Clinicopathological study of 1000 biopsied gingival lesions among dental outpatients: a 22-year retrospective study - Mohammad-Salar Montaze; Golnoush Farzinnia; Zohreh Jaafari-Ashkavandi (BMC, 2022)
Abstract Background Up to now, limited research has been done on a significant number of cases with all types of gingival lesion. Besides, the available literature does not provide reliable data on the epidemiology of gingival lesions, especially non-reactive lesions. Thus, the present study aimed to analyze the frequency and distribution of gingival lesions in an Iranian population. Methods This retrospective study was conducted on 1000 gingival biopsy samples during 22 years. All lesion types were evaluated in terms of location, clinical signs and symptoms, and patients' age and gender. The data were analyzed using descriptive statistics and chi-square test. Results Out of the 5284 oral lesions, 1000 (18.92%) gingival lesions were detected, with a female dominance (64.06%). The incidence peak (35.6%) was observed in the third and fourth decades. Non-neoplastic lesions accounted for 92.4% of the cases. The most common reports were related to reactive lesions (71.8%), with the highest prevalence being related to pyogenic granuloma. Additionally, oral squamous cell carcinoma (OSCC) was the most common neoplasm, and exophytic changes and color changes were the most frequent clinical signs. Conclusions The study findings indicated the high prevalence of gingival pathological lesions. Although most biopsies were reactive in nature, a few cases were malignant, which must be considered by practitioners. Further research is needed to achieve a clear impression about non-neoplastic lesions so as to develop more helpful oral health planning.